2000
DOI: 10.1063/1.1287634
|View full text |Cite
|
Sign up to set email alerts
|

Apparatus for in situ x-ray absorption fine structure studies on catalytic systems in the energy range 1000 eV<E<3500 eV

Abstract: A new apparatus for in situ x-ray absoprtion fine structure measurements in the medium energy range of 1000–3500 eV has been developed. Measurements can be performed in a gaseous environment (max. pressure 1 bar) at temperatures ranging from 80 to 750 K. Pre-treatments can be performed at 5 bar and 750 K in the same cell, after which XAFS measurements can be done without exposing the sample to ambient air. In a modular set-up several detector systems can be used: fluorescence detection using a gas proportional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…This is ascribed to the differences in the measurements conditions, i.e., high vacuum (Al XAS) versus strongly hydrated state ( 27 Al MAS NMR). When water is removed from the pores of the zeolite, only tetrahedral aluminum is present [28]. From the results presented it is concluded that no significant changes occurred to the aluminum coordination during the synthesis, even after applying a severe calcination procedure.…”
Section: Al Mas Nmr Al K-edge Xafsmentioning
confidence: 70%
See 1 more Smart Citation
“…This is ascribed to the differences in the measurements conditions, i.e., high vacuum (Al XAS) versus strongly hydrated state ( 27 Al MAS NMR). When water is removed from the pores of the zeolite, only tetrahedral aluminum is present [28]. From the results presented it is concluded that no significant changes occurred to the aluminum coordination during the synthesis, even after applying a severe calcination procedure.…”
Section: Al Mas Nmr Al K-edge Xafsmentioning
confidence: 70%
“…Data were collected at station 3.4 of the SRS Daresbury (UK), using a double crystal monochromator equipped with YB66 crystals. A recently developed in situ low energy X-ray absorption fine structure spectroscopy set-up (ILEX-AFS) was used [27,28]. The samples were pressed into selfsupporting wafers and measured at room temperature under high vacuum (P < 10 −5 bar).…”
Section: Al Mas Nmr Al K-edge Xafsmentioning
confidence: 99%
“…An in-situ XAS cell designed for catalyst studies in the intermediate energy range of 1000-3500 eV has also been reported. 7 XAS data are collected by either fluorescence or electron-yield detection at pressures of 10 -4 atm to 1 atm and temperatures of 80 K to 750 K. While this apparatus has proven useful for studying the K-edge of metals such as Mg, Al, and Si, there is a growing interest in exploring electronic transitions occurring below 1000 eV. 8,9 This range includes the Kedge of low Z elements 6<Z<10 such as oxygen and the L-edge of 3d and M-edge of 4d transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Since the cell is designed for 4 transmission measurements, the type of material studied is not limited, as is the case for total electron yield measurements, to samples with adequate electrical conductance. 7 Hence, this cell can be used to characterize the O K-edge and the L edges or M edges of 3d or 4d transition metals, respectively, and their oxides supported on non-conducting supports.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by research in catalysis, an in situ cell for the energy range from 1000 to 3500 eV was developed. 10,11 Further approaches are summarized in Refs. 12 and 13.…”
Section: Introductionmentioning
confidence: 99%